Effect of oilseed roasting on the quality, flavor and safety of oil: A comprehensive review. (December 2021) - Zhang, Yu; Li, Xiaolong; Lu, Xinzhu; Sun, Hao; Wang, Fengjun
Graphical abstract: Highlights: Moderate roasting improves extraction of bioactive compounds. Oils from appropriate roasting exhibit better stability and pleasant flavor. Roasting condition must be controlled to avoid exceeding limitation of PAHs. Appropriate roasting should be determined by quality, flavor and safety of oil. Nutrition and safety evaluation of roasted oil require in vivo assay. Abstract: Roasting is widely applied in oil processing and employs high temperatures (90–260 °C) to heat oilseeds evenly. Roasting improves the extraction yield of oil by the generation of pores in the oilseed cell walls, which facilitates the movement of oil from oilseed during subsequent extraction. It also affects the nutritional value and palatability of the prepared oil, which has attracted consumers' attention. An appropriate roasting process contributes to better extraction of bioactive compounds, particularly increasing the total polyphenol content in the oil. Correspondingly, extracted oil exhibits higher antioxidant capacity and oxidative stability after roasting the oilseeds due to better extraction of endogenous antioxidants and the generation of Maillard reaction products. Furthermore, roasting process is critical for the formation of aroma-active volatiles and the improvement of desired sensory characteristics, so it is indispensable for the production of fragrant oil. However, some harmful components are inevitably generated during roasting, including oxidation products, polycyclic aromatic hydrocarbons, and acrylamide. Monitoring and controlling the concentrations of harmful compounds in the oil during the roasting process is important. Therefore, this review updates how roasting affect the quality and safety of oils and provides useful insight into regulation of the roasting process based on bioactive compounds, sensory characteristics, and safety of oils. Further research is required to assess the nutritional value and safety of roasted oils in vivo and to develop a customized roasting process for various oilseeds to produce good-quality oils.